Molecular screening of septoria-resistant genes in historical Turkish bread wheat germplasm using the validated gene specific SSR markers - Ali, Amjad; Ölmez, Fatih; Tatar, Muhammed; Mortazavi, Parnaz; Altaf, Muhammad Tanveer; Turgay, Emine Burcu; Aktas, Hüsnü; Nadeem, Muhammad Azhar; Javed, Jazib; Gou, Jinying; Aasim, Muhammad; Dababat, Abdelfattah A.S.; et al. (Tubitak, 2025)
Septoria tritici blotch (STB), caused by Zymoseptoria tritici, poses a significant threat to global wheat production, particularly in Türkiye. Resistance breeding is the most sustainable and effective disease control method. Molecular markers, especially simple sequence repeat (SSR) markers are extensively employed in wheat breeding to enhance the efficacy. The primary objective of this study was to identify Stb resistance genes among 143 historical registered Turkish bread wheat genotypes released as commercial cultivars between 1963 to 2014, using 16 closely linked SSR markers. The findings revealed substantial genetic variation among the screened cultivars, with the Stb3 gene being the most prevalent, identified in 89.51% of the samples. Other notable resistant genes included Stb13 (71.32%), Stb4 (43.33%), and Stb11 (41.25%). Cultivars Porsuk-2811, Porsuk-2853, and Porsuk-2868 exhibited the highest level of resistance to STB, with 10 resistance genes detected. Of the 143 cultivars screened, 10 were found to carry a total of nine Stb genes, while two cultivars were observed to possess only a single resistance gene. The study identified 23 wheat cultivars harboring 8-10 Stb resistance genes, which are highly recommended for future wheat breeding programs and gene pyramiding strategies to combat Z. tritici. This research provides critical insights for national breeding programs, supporting the development of resilient and high-yielding wheat varieties resistant to STB.